The weight of ideology on the attitude of Latin American countriestoward the United States - Botelho, João Carlos Amoroso (2017)
The article tests the effect of ideology on the attitude of Latin American countries toward the United States, as well as alternative explanations, to respond to the expectation that left-wing governments are critical of the US and right-wing governments are friendly. The findings are that the alternative explanations are less relevant and that ideology has the expected effect.